Taxonomy and uses of Daemonorops draco (Willd.) Blume - Himmah Rustiami; Francisca M. Setyowati; Kuswata Kartawinata (The Ethnobiological Society of Indonesia, 2004)
Dragon's blood group or locally known as rotan iernang distribute from Malay Peninsula, Sumatra, Borneo to Java. Ten species are recognized formerly but only Daemonorops draco (Wild.) Blume is very well known worldwide and widespread in Sumatra. Sometimes botanist regarded this species to other related species. Red resin on its fruit scales have been used by Anal Dalani and Talang Mamak tribes from Bukit Tiga Puluh National Park as dying or furnishing. Unfortunately, taxonomic status of this species is doubtful because of the fact that more than a century there is no clear type addressed to this species. New type of Daemonorops draco Blume is designated here together with the distribution and ecology, and economic botany information.",